Iṉavātattiṟku viṭivu eṉṉa? - Perairā, Vi. El (Malaiyaka Iḷaiñar Pēravai, 1978)
An account of the August 1977 insurrection against Tamils in Jaffna District, Sri Lanka, and suggestions to overcome the problems.